1984
DOI: 10.1111/j.1528-1157.1984.tb03486.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Seizure Activity Produce Purkinje Cell Loss?

Abstract: Eight Wistar rats were exposed to 140 electroconvulsive seizures over 50 days. Ten rats served as controls. The density of Purkinje cells in cerebellum ranged from 15.3 to 18.5/mm in the treated rats and from 15.2 to 19.1/mm in the controls. No Purkinje cell loss was disclosed in the rats subjected to electroconvulsive seizures. Twenty-five Mongolian gerbils of the seizure-susceptible strain were selected according to seizure score with five animals in each group. Five Mongolian gerbils of a seizure-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…Several hypotheses about the mechanism of volume reduction in the cerebellum have been postulated. These include seizure-induced damage (e.g., hypoxia), the effects of AEDs (e.g., phenytoin), and the potential effects of initial etiological insults and early neurodevelopmental factors [10,28,29]. However, the studies that include patients with CHE did not show a causal relationship between the pre-existing anatomic abnormalities in the cerebellum with the onset of epilepsy.…”
Section: Discussionmentioning
confidence: 87%
“…Several hypotheses about the mechanism of volume reduction in the cerebellum have been postulated. These include seizure-induced damage (e.g., hypoxia), the effects of AEDs (e.g., phenytoin), and the potential effects of initial etiological insults and early neurodevelopmental factors [10,28,29]. However, the studies that include patients with CHE did not show a causal relationship between the pre-existing anatomic abnormalities in the cerebellum with the onset of epilepsy.…”
Section: Discussionmentioning
confidence: 87%
“…Quantitative studies of unmodified ECS in rats found no effects on neuronal number in neocortex (Colon and Notermans, 1975), hippocampus (Dam et al, 1980; Gombos et al, 1999; Laursen et al, 1991), cerebellum (Dam et al, 1984), or thalamus (Laursen et al, 1991; Vaidya et al, 1999). In the only stereological study to include hippocampal granular cell neurons, these were greater in number, and the granular cell layer and hilus were greater in volume, in rats receiving daily unmodified ECS for 10 days, compared with rats receiving sham treatments; CA1 and CA2–3 were unaffected (Chen et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the cerebellar Purkinje cells displayed the highest relative amount of nDNA SSB of all investigated cell types (in young animals approximately three times more than the hippocampal pyramidal cells; [10]) although the relative amount of nDNA repair was comparable among Purkinje cells and hippocampal pyramidal cells [20]. The high relative amount of nDNA SSB observed in Purkinje cells was most probably due to the fact that these cells are among the largest neurons in the CNS and have an exceptionally high metabolic demand [89][90][91]. On the other hand, this high metabolic demand has also been hypothesized to be involved in the high vulnerability of Purkinje cells under conditions such as acute hypoxia or seizures [89][90][91].…”
Section: Age-related Accumulation Of Ndna Damage and Decline In Ndna mentioning
confidence: 91%
“…The high relative amount of nDNA SSB observed in Purkinje cells was most probably due to the fact that these cells are among the largest neurons in the CNS and have an exceptionally high metabolic demand [89][90][91]. On the other hand, this high metabolic demand has also been hypothesized to be involved in the high vulnerability of Purkinje cells under conditions such as acute hypoxia or seizures [89][90][91]. Based on these data we have hypothesized that the lack of age-related increase in the relative amount of nDNA SSB in Purkinje cells does not reflect an exception from Gensler and Bernstein's [86] hypothesis but rather indicates a fundamental difference in the selective neuronal vulnerability of Purkinje cells during aging compared to the other types of neurons mentioned above.…”
Section: Age-related Accumulation Of Ndna Damage and Decline In Ndna mentioning
confidence: 99%